Characterizing the digital planetarium as a teaching and learning space - Sivitilli, Alexander (Department of Astronomy, 2024)
The modern planetarium exists today as a digital immersive facility with a multitude of capabilities and applications while also being tied to its analog roots among instructional media in astronomy education. I characterized the use of the digital planetarium as a teaching and learning space by following two lines of inquiry: a) how students engage with a digital planetarium and b) what shapes the teaching and learning space in the planetarium. For these two questions, two sources of data respectively formed the basis of the investigation: student responses and observational data. The data were analyzed using the Grounded Theory Method. Student responses were gathered from a cohort of university students during two separate planetarium visits which constituted part of their introductory astronomy course. An instrument was designed to probe both how the students responded to the overall planetarium experience and how they engaged with the educational content. In the second student visit, the show content was specifically designed by me, and the instrument had been modified based on the results of the first visit. Individual student responses were analyzed for key ideas which were grouped into several categories that emerged from the data. These categories allowed me to develop a localized mid-level model of student engagement. This led to the notion of a “spectrum of attentiveness” that strongly influenced how students engaged. The data also suggested an optimal level for relevant engagement that was influenced by the nature of coincident distractions. Detailed observations were documented throughout the investigation that included multiple additional visits to the planetarium. These visits familiarized me with the planetarium and its use as an educational space. Categories were constructed from the observational data, allowing the development of a second localized mid-level model that described the key contextual factors that influenced the planetarium teaching and learning space. In addition to addressing the initial lines of inquiry, the localized models were then supplemented with broader cognitive models, in particular Working Memory (WM) and Cognitive Load Theory (CLT). By combining both models with the explanatory power from WM and CLT, a Model for Curriculum Design in the Planetarium (MCDiP) was developed to systematically shape the digital planetarium as an effective teaching and learning space.